2012
DOI: 10.1111/j.1438-8677.2011.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of candidate DNA barcodes for identifying non‐flowering seed plants

Abstract: In plants, matK and rbcL have been selected as core barcodes by the Consortium for the Barcode of Life (CBOL) Plant Working Group (PWG), and ITS/ITS2 and psbA-trnH were suggested as supplementary loci. Yet, research on DNA barcoding of non-flowering seed plants has been less extensive, and the evaluation of DNA barcodes in this division has been limited thus far. Here, we evaluated seven markers (psbA-trnH, matK, rbcL, rpoB, rpoC1, ITS and ITS2) from non-flowering seed plants. The usefulness of each region was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Genetic techniques for species identification based on multiple genes (rbcL & matK for plants; COBL Plant Working Group, 2009) or single-gene (CO1 for animal; Hebert et al, 2003) sequence similarity or phylogenies have been rapidly gaining wide use. BLAST, the nearest distance/similarity of sequences and phylogenetic tree based method have been used as bioinformatics tools along with molecular techniques for the identification of plants (Liu et al, 2012a;Liu et al, 2012b;Pang et al, 2012). In this study, BLAST search using both rbcL and matK primarily identified the query specimen as C. murale except BOLD search with matK gene sequence, which misidentified the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic techniques for species identification based on multiple genes (rbcL & matK for plants; COBL Plant Working Group, 2009) or single-gene (CO1 for animal; Hebert et al, 2003) sequence similarity or phylogenies have been rapidly gaining wide use. BLAST, the nearest distance/similarity of sequences and phylogenetic tree based method have been used as bioinformatics tools along with molecular techniques for the identification of plants (Liu et al, 2012a;Liu et al, 2012b;Pang et al, 2012). In this study, BLAST search using both rbcL and matK primarily identified the query specimen as C. murale except BOLD search with matK gene sequence, which misidentified the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…The single pair of rbcL primers we used worked in gymnosperms, lycophytes, monilophytes, and angiosperms, as other studies have also found (e.g., [34]). Although other primers have been used to recover rbcL from ferns [87,96] and gymnosperms in DNA barcoding studies (e.g., [166]), a single set of primers that will amplify rbcL across land plants is of great practical use, facilitating recovery of the region from any unknown sample. In angiosperms, rbcL was recovered from an equal or greater number of samples per family than matK , except in Boraginaceae, in which rbcL was recovered from just one of 11 samples, which all worked for matK (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Procurement of materials from other plant species was described previously [14], [71], [72]. Genomic DNA extraction was performed using the Plant Genomic DNA Extraction Kit according to the manufacturer′s protocol (Tiangen Biotech Co., China).…”
Section: Methodsmentioning
confidence: 99%